A multidisciplinary framework for research prioritization at the science-policy interface: Insights for wildlife conservation and management - Nikol Damato; Alex McInturff (Environmental Science & Policy, 2025)

Coexistence beyond disciplinary silos: Five dimensions of analysis for more convivial human-predator interactions - Judith E. Krauss; Valentina Fiasco; Silvio Marchini; Alex McInturff; Laila T. Sandroni; Peter S. Alagona; Dan Brockington; Bram Büscher; Rosaleen Duffy; Katia Maria P M de Barros Ferraz; Rob Fletcher; Wilhelm Andrew Kiwango; et al. (Biological Conservation, 2025)

Triangulating habitat suitability for the locally extirpated California grizzly bear - Alex McInturff; Peter S. Alagona; Scott D. Cooper; Kaitlyn M. Gaynor; Sarah E. Anderson; Elizabeth S. Forbes; Robert Heilmayr; Elizabeth H.T. Hiroyasu; Bruce E. Kendall; Alexis M. Mychajliw; Molly Hardesty-Moore (Biological Conservation, 2025)

The production-protection nexus: How political-economic processes influence prospects for transformative change in human-wildlife interactions - Robert Fletcher; Kate Massarella; Katia M.P.M.B. Ferraz; Wilhelm A. Kiwango; Sanna Komi; Mathew B. Mabele; Silvio Marchini; Anja Nygren; Laila T. Sandroni; Peter S. Alagona; Alex McInturff (Global Environmental Change, 2023)

Back to the future: Indigenous relationality, kincentricity and the North American Model of wildlife management - Deniss J. Martinez; Clare E.B. Cannon; Alex McInturff; Peter S. Alagona; David N. Pellow (Environmental Science & Policy, 2023)

Identifying individual ungulates from fecal DNA: a comparison of field collection methods to maximize efficiency, ease, and success - Bryan H. Bach; Ashling B. Quigley; Kaitlyn M. Gaynor; Alex McInturff; Kristin L. Charles; Janelle Dorcy; Justin S. Brashares (Mammalian Biology, 2022)
Non-invasive genetic sampling can facilitate the identification of individual animals across a landscape, with applications to management and conservation. Fecal material is a readily available source of DNA, and various methods exist for collecting fecal samples for DNA preservation. In particular, swab methods offer considerable promise, but their utility in real-world field contexts remains relatively untested. We systematically compared multiple genetic fecal sampling methods across all stages of data collection and analysis, including sampling in the field, DNA extraction in the lab, and identification of individuals using microsatellite genotyping. We collected 112 fecal samples from black-tailed deer ( Odocoileus hemionus columbianus ) in the field in Mendocino County, California, across a range of sample conditions of unknown age. We systematically compared the efficiency, ease, and genotyping success of three methods for field collection and storage of ungulate fecal samples: whole pellets in ethanol, whole dry pellets in paper envelopes, and cotton swabs in buffer. Storage method, sample condition, and their interaction predicted genotyping success in the top binomial GLMMs. We found that swabbing pellets resulted in the greatest percentage of individually identifiable genotypes (81%, compared to 60% for dry samples and 56% for ethanol), despite lower DNA concentrations. While swabbing pellets requires a greater time investment in the field, the samples are easier and safer to store and transport, and subsequent labwork is more efficient as compared to whole-pellet collection methods. We, therefore, recommend the swab method for most contexts. We provide additional recommendations and field protocols based on subsequent collection of 2284 swab samples for a larger monitoring study of the deer population, given that this large number of samples spanned a range of sample conditions and time spent in storage.

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

An ecological framework for contextualizing carnivore–livestock conflict - Christine E. Wilkinson; Alex McInturff; Jennifer R. B. Miller; Veronica Yovovich; Kaitlyn M. Gaynor; Kendall Calhoun; Harshad Karandikar; Jeff Vance Martin; Phoebe Parker‐Shames; Avery Shawler; Amy Van Scoyoc; Justin S. Brashares (Conservation Biology, 2020)
Carnivore predation on livestock is a complex management and policy challenge, yet it is also intrinsically an ecological interaction between predators and prey. Human–wildlife interactions occur in socioecological systems in which human and environmental processes are closely linked. However, underlying human–wildlife conflict and key to unpacking its complexity are concrete and identifiable ecological mechanisms that lead to predation events. To better understand how ecological theory accords with interactions between wild predators and domestic prey, we developed a framework to describe ecological drivers of predation on livestock. We based this framework on foundational ecological theory and current research on interactions between predators and domestic prey. We used this framework to examine ecological mechanisms (e.g., density‐mediated effects, behaviorally mediated effects, and optimal foraging theory) through which specific management interventions operate, and we analyzed the ecological determinants of failure and success of management interventions in 3 case studies: snow leopards ( Panthera uncia ), wolves ( Canis lupus ), and cougars ( Puma concolor ). The varied, context‐dependent successes and failures of the management interventions in these case studies demonstrated the utility of using an ecological framework to ground research and management of carnivore–livestock conflict. Mitigation of human–wildlife conflict appears to require an understanding of how fundamental ecological theories work within domestic predator–prey systems.